Pengembangan Lembar Kerja Peserta Didik (LKPD) Matematika Materi Pecahan Menggunakan Model Problem Based Learning di Kelas IV Sekolah Dasar - sri zuriatin; Agus Susanta; Abdul Muktadir (Universitas Bengkulu, 2022)
ABSTRACT This research aims to produce LKPD Mathematics fractional material using problem based learning models in grade IV SDN 48 Lubuklinggau, LKPD eligibility, student response to LKPD and teacher response to LKPD. This research is a development research (Reseach and Development) and addie model development model. The stages of research consist of five stages, namely analysis, design, develop, implementation and evaluation. This research is only carried out until the implementation stage, namely the validity test and reliability test. The instruments used in this study are the validity test questionnaire and the reliability test questionnaire. The validity test was conducted by 6 validators, namely 2 Material Experts, 2 Linguists and 2 Media Experts. Reliability test was conducted on 15 students of grade IV SDN 48 Lubuklinggau. Data Analysis using Aiken's V. Results of LKPD Mathematics feasibility test with PBL model by validators in terms of aspects, material feasibility, language presentation, and ballisticity feasibility, material feasibility obtained (0.78) with appropriate criteria, language eligibility results (0.81) with very feasible criteria and results of graphing eligibility (0.79). The results of the LKPD Mathematics field test with the PBL model, obtained good assessment by teachers and excellent by learners with decent criteria. It can be concluded that LKPD Mathematics fractional material using the PBL model in SDN 48 Lubuklinggau class IV is declared feasible.